Plasticidad fenotípica para rendimiento en grano y rasgos relacionados en líneas e híbridos de maíz cultivados en regímenes hídricos contrastantes - Ruiz, Monica Beatriz; D'Andrea, Karina Elizabeth; Otegui, María Elena (Asociación de Ingenieros Agrónomos del Norte de la Provincia de Buenos Aires (AIANBA), 2020)
Phenotypic plasticity (PP) refers to the variation range of a trait in response to changes in the environment. Traits with low PP are classified as stable, whereas those with high PP are considered plastic. The objective of current research was to evaluate PP variation in grain yield (GY) and related traits among maize inbreds (I) and hybrids (H) grown under high (WW) and low (WD) water availabilities and compare it with our previous reports for N stress. Measured traits were thermal time to 50% anthesis (TTA) and silking (TTS), the anthesis-silking interval in days (ASID) and in TT (ASITT), plant height (Ph), prolificacy (Pr), GY, kernel numbers (KN), and kernel weight (KW). Data were normalized respect to the median value of each genotype group and PP computed as the difference between percentiles 90% (P90) and 10% (P10). As previously registered for N stress, WW data corresponded to P90 and WD to P10, except for ASIs (opposite trend). I and H did not differ in PP only for Ph, KW and ASITT. A large plasticity (PP>1) was verified (i) for ASIs, GY and KN in response to water availability, and (ii) only for ASIs in response to N availability.